INTERACTION INDICATORS BETWEEN PLANT AND ENVIRONMENT DATE PALM (PHOENIX DACTYLIFERA) AS AN EXAMPLE - Mohammed A.H. Alnajjar; Wurood H. Neamah; Wasen F.F.Alapresam; Fatin H. Al-Dulaimi (European Journal of Agricultural and Rural Education, 2022)
Ecosystem is a branch of biology concerning a study the interaction between living organisms and the environment where they live. Each plant community has a special range of eco-conditions that could be wide or narrow depending on biotic, and abiotic factors. Date palm phoenix dactylifera is the most important palm species in Arecaceae family and is the most popular and historic fruit tree in Iraq and Arabic gulf area, it’s considered the best example of the interaction between environment and plant. Over years, phoenix dactylifera modified some phenotypical and anatomical features in leaves as one of a response form for environmental stress such as length and width of leaflets as well as cuticle and epidermis layers. These modifications have an important role in the tree adaption to environmental stress such as drought, salinity and high temperature. Also, one of plant methods to stress resistance is a synthesis of effectible molecules that help in adaptation mechanism of grown plants under stress conditions Thus, study the protein pattern of pollen of phoenix dactylifera that are grown in different environments show significant differences in the number, frequency and molecular weight of protein bands in the pollen grains. The current review displayed how a wide response of date palm tree to environmental changes characterized robustly the interaction between plants and the environment in nature